2011
DOI: 10.1186/1472-6882-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine at Norwegian and Danish hospitals

Abstract: BackgroundSeveral studies have found that a high proportion of the population in western countries use complementary and alternative medicine (CAM). However, little is known about whether CAM is offered in hospitals. The aim of this study was to describe to what extent CAM is offered in Norwegian and Danish hospitals and investigate possible changes in Norway since 2001.MethodsA one-page questionnaire was sent to all included hospitals in both countries. The questionnaire was sent to the person responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 8 publications
0
51
1
14
Order By: Relevance
“…Yet, dermatologists are still unfamiliar with it and most of them have some misconceptions. The popularity of CAM continued to grow in developed countries such as USA, Norway during the first decade on the 21st century [11,12,13]. This might indicate a shift in attitude regarding CAM within the conventional health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, dermatologists are still unfamiliar with it and most of them have some misconceptions. The popularity of CAM continued to grow in developed countries such as USA, Norway during the first decade on the 21st century [11,12,13]. This might indicate a shift in attitude regarding CAM within the conventional health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Embora a acupuntura seja reconhecida como especialidade médica pelo Conselho Federal de Medicina desde 1995 1 , seja indicada pela Organização Mundial da Saúde para uma grande gama de patologias 2 e tenha sido observado um aumento no número de adeptos, por parte tanto dos profissionais como dos pacientes [3][4][5][6][7] , no Brasil o seu ensino nas escolas médicas ainda é reduzido, mesmo após a publicação da Portaria 971, que criou a Política Nacional de Práticas Integrativas e Complementares no Sistema Único de Saúde 8 . As Práticas Integrativas e Complementares (PIC), previamente conhecidas como Medicina Alternativa, em geral adotam uma abordagem do processo saúde-doença-cuidado mais holística que a medicina ocidental contemporânea 8 .…”
Section: Introductionunclassified
“…A acupuntura, uma das terapêu-ticas da MTC, data de mais de três mil anos e baseia-se na existência de um equilíbrio energético corporal, em que as doenças são encaradas como desequilíbrios, e o tratamento, como devolução deste equilíbrio pela modulação dos fluxos energéticos [9][10] . Atualmente, na Noruega e Dinamarca, respectivamente, 40% e 25% dos hospitais oferecem acupuntura a seus pacientes, sendo este serviço o mais relevante dentro das PIC naqueles países 3 . Nos EUA, observou-se um aumento significativo na procura desse tipo de tratamento, especialmente em decorrência da falta de acesso aos tratamentos convencionais ou em casos em que estes não atenderam às necessidades dos pacientes, assumindo, então, a acupuntura papel complementar 4 .…”
Section: Introductionunclassified
“…A similar difference applies to Danish conditions; the Danish-Norwegian study found that CAM was used in 31% of Danish hospitals, distributed among two CAM modalities, when the chief physicians at hospital management level were asked. However, massage was not included as a CAM modality in the Danish-Norwegian study [12] . If the use of massage is precluded from the current study, CAM is used in 33.8% of the Danish hospitals, represented by 23 different CAM modalities.…”
Section: Chief Physicians and Department Nurses As Respondentsmentioning
confidence: 99%